Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/cas.14607
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation cancer therapy using hydrophilic block copolymers conjugated with deferoxamine

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 57 publications
(117 reference statements)
4
49
1
Order By: Relevance
“…In another recent study, Komoto et al [ 154 ] revealed the first success of the design of polymeric DFO for the enhancement of iron chelation cancer therapy. They developed polymeric DFO by the covalent conjugation of DFO to poly(ethylene glycol)poly(aspartic acid) (PEGPAsp) block copolymers.…”
Section: Combined Therapy With More Than One Chelatormentioning
confidence: 99%
“…In another recent study, Komoto et al [ 154 ] revealed the first success of the design of polymeric DFO for the enhancement of iron chelation cancer therapy. They developed polymeric DFO by the covalent conjugation of DFO to poly(ethylene glycol)poly(aspartic acid) (PEGPAsp) block copolymers.…”
Section: Combined Therapy With More Than One Chelatormentioning
confidence: 99%
“…DFO is also capable of inhibiting hRR activity by chelating Fe III , forming a 1:1 ligand–metal complex [ 218 ]. While DFO does not directly affect the hRRM2 subunit, sequestration of intracellular iron prevents the activation and regeneration of the tyrosyl radical center, thus inhibiting hRR activity [ 219 , 220 , 221 ]. This inhibition is reversible with the addition of iron and appears to affect p53R2 more potently than hRRM2.…”
Section: Non-nucleoside Inhibitors Of Hrrm2mentioning
confidence: 99%
“…DFO binds Fe 3+ within cells or free plasma Fe 3+ , creating a complex (ferrioxamine) that is redox and metabolically inert [ 36 ]. Once DFO binds intracellular iron [ 49 ], it is then released from cells and excreted primarily in the urine, with a small component entering the bile and feces, resulting in whole-body iron depletion [ 50 ]. While DFO has been demonstrated to inhibit neuroblastoma cell lines in vitro [ 36 , 47 ], it is less effective in vivo due to its rapid metabolism and poor lipophilicity, which limits its ability to enter cells [ 36 ].…”
Section: Cancer Therapy Using the Metal-binding Ligands Dfo And Thiosemicarbazones Dp44mt And Dpcmentioning
confidence: 99%